2016
DOI: 10.24036/02016516477-0-00
|View full text |Cite
|
Sign up to set email alerts
|

Kontribusi Konsep Diri Dan Dukungan Orangtua Terhadap Motivasi Belajar Siswa Dan Implikasinya Dalam Pelayanan Bimbingan Dan Konseling

Abstract: The research was backgrounded by still low level of the learning motivation of students. The self-concept and parental support suspectted to affect the learning motivation of students. This research aims to describe : (1) the self-concepts, (2) parental support, (3) learning motivation of students, (4) the contribution of the self-concept toward the learning motivation of students, (5) the parental support contributions toward the learning motivation of students, and (6) the contribution of self-concept and pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
4
0
12

Year Published

2018
2018
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 0 publications
3
4
0
12
Order By: Relevance
“…It meant that self-concept and parental support were factors related to learning motivation of the students who were expelled from their previous schools. The results of this study are supported by research conducted by Saragi, M. P. D., Iswari, M. & Mudjiran (2016) namely that there is a significant relationship between self-concept and parental support together with student learning motivation. The higher the self-concept and parental support received by students, the higher the motivation of student learning, and vice versa if the self-concept and parental support are low, then student motivation will also below.…”
Section: Learning Motivationsupporting
confidence: 80%
See 1 more Smart Citation
“…It meant that self-concept and parental support were factors related to learning motivation of the students who were expelled from their previous schools. The results of this study are supported by research conducted by Saragi, M. P. D., Iswari, M. & Mudjiran (2016) namely that there is a significant relationship between self-concept and parental support together with student learning motivation. The higher the self-concept and parental support received by students, the higher the motivation of student learning, and vice versa if the self-concept and parental support are low, then student motivation will also below.…”
Section: Learning Motivationsupporting
confidence: 80%
“…The higher the self-concept, the higher the student's motivation to learn. Furthermore, Saragi, M. P. D., Iswari, M. & Mudjiran (2016) research also revealed that self-concept contributes to students' learning motivation by 24.2%. That is, the higher the contribution of students' self-concepts, the higher the student's motivation to learn.…”
Section: Learning Motivationmentioning
confidence: 94%
“…Based on the results of the descriptive analysis, overall, students' learning motivation in mathematics subjects in MAN 1 Pekanbaru is in the high category. The results of this study supported by Saragi (2016)&Putri (2016 show that students' motivation is in the high category. Although the results of the study showed that most of the research samples had high motivation to study in mathematics, there were still respondents in the medium, low to very low categories.…”
Section: Learning Motivationsupporting
confidence: 73%
“…Hasil penelitian sebelumnya menunjukkan konsep diri dipengaruhi oleh beberapa faktor, yaitu pendidikan, pola asuh, hubungan guruanak (Putri, 2012), praktik pengasuhan, interaksi keluarga (Brown, Mangelsdorf, Neff, Schoppe-Sulivan, & Frosch, 2009), jenis kelamin anak serta pendidikan orang tua (Matovu, 2012;Polat & Aksin, 2015). Selain itu, konsep diri juga mampu memengaruhi motivasi dan prestasi belajar (Saragi, Iswari, & Mudjiran, 2016;Sewasew, Schroeders, Schiefer, Weirich, & Artelt, 2018).…”
Section: Berdasarkanunclassified